ANALISA RASIO PERPUTARAN PERSEDIAAN BUSANA MUSLIM TERHADAP JUMLAH PENJUALAN BULANAN PADA PT. TATA BUSANA DI JAKARTA - Dwiyatmoko Pujiwidodo (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2014)
Current economic developments resulted in a business activity that is increasingly faced with complex problems and dynamic. To deal with these problems, the company is expected to innovative and capable of adapting to the changes that occur. In a trading company, the ability to store enough supplies to meet the needs of customers can be a very complex problem. Failure to do so could result in loss of sales. On the other hand, too much supply store will be able to increase the risk of losses due to the price reduction, damage or changes in customer buying patterns. Merchandise inventory and sales at PT. Dressmaking decline and rise every month, this is because the Muslim fashion market conditions uncertain. Therefore, it is necessary to analyze the inventory turnover Muslim clothing at. Dressmaking so as to know how much inventory will be sold each month. Data obtained by using techniques of documentation and observation. Analysis of the data using the formula inventory turnover ratio and average days - average inventory. PT. Tata Busana is a company engaged in the field of Muslim fashion retail. The results of the analysis as follows: (1). Inventory turnover is always increase except in September to December. (2) The level of sales is also always increase except in August, September and December Keywords : Day Average - Average Inventory, Inventory Turnover Ratio, Sales